2009
DOI: 10.1002/hipo.20641
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal lobe activity during complex discrimination of faces, objects, and scenes: Effects of viewpoint

Abstract: The medial temporal lobe (MTL), a set of heavily interconnected structures including the hippocampus and underlying entorhinal, perirhinal and parahippocampal cortex, is traditionally believed to be part of a unitary system dedicated to declarative memory. Recent studies, however, demonstrated perceptual impairments in amnesic individuals with MTL damage, with hippocampal lesions causing scene discrimination deficits, and perirhinal lesions causing object and face discrimination deficits. The degree of impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
199
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 158 publications
(222 citation statements)
references
References 50 publications
20
199
3
Order By: Relevance
“…Unlike several previous studies that have looked at HC responses during scene perception [Barense et al, 2010; Lee et al, 2008; Lee and Rudebeck, 2010b; Mundy et al, 2012; Zeidman et al, 2015], we found stronger group‐level (bilateral) activation in the anterior, rather than posterior, HC (although see Lee et al, 2013). As has been discussed elsewhere, spatial smoothing of EPI data can lead to “blurring” between adjacent anatomical ROIs, such as between PHG and posterior HC [Reber et al, 2002].…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Unlike several previous studies that have looked at HC responses during scene perception [Barense et al, 2010; Lee et al, 2008; Lee and Rudebeck, 2010b; Mundy et al, 2012; Zeidman et al, 2015], we found stronger group‐level (bilateral) activation in the anterior, rather than posterior, HC (although see Lee et al, 2013). As has been discussed elsewhere, spatial smoothing of EPI data can lead to “blurring” between adjacent anatomical ROIs, such as between PHG and posterior HC [Reber et al, 2002].…”
Section: Discussioncontrasting
confidence: 93%
“…Critically, this one‐back localiser task, which involved rapidly presented scenes with minimal mnemonic demand, yielded strong ( Z  > 7) bilateral activation in the HC bilaterally, supporting a task‐independent role of the HC in complex scene processing [Barense et al, 2010; Lee et al, 2008; Lee and Rudebeck, 2010b]. Unlike several previous studies that have looked at HC responses during scene perception [Barense et al, 2010; Lee et al, 2008; Lee and Rudebeck, 2010b; Mundy et al, 2012; Zeidman et al, 2015], we found stronger group‐level (bilateral) activation in the anterior, rather than posterior, HC (although see Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations